POTENTIAL OF ENTOMOPATHOGENIC FUNGI FOR BIOCONTROL OF SPODOPTERA LITURA FABRICIUS (L EPIDOPTERA: NOCTUIDAE) - M. R. Asi; M. H. Bashir; M. Afzal; K. Zia; M. Akram (Journal of Animal and Plant Sciences, 2013)
Susceptibility of different biological stages of Spodoptera litura to various strains of entomopathogenic fungi was evaluated under laboratory conditions at Department of Entomology University of Agriculture, Faisalabad using the insect immersion method. Virulence potential of the entomopathogenic fungi varied with different biological stages of the insect pest. Eggs and larvae were comparatively more susceptible to infections by entomopathogenic fungi, while pupae were less susceptible. The susceptibility of the insect to entomopathogenic fungi decreased with the advancement in age of larvae of the insect. The LC50 values for eggs were 1.13×106 , 4.82×106 and 2.45×107conidia ml-1 in M. anisopliae L6, I. fumosorosea 32 and B. bassiana 25, respectively. The median lethal concentration (LC50) for 3rd instar larvae was 1.11×107conidia ml-1 in B. bassiana 25 and 2.17×107conidia ml-1 in I. fumosorosea 32. Mortality of the larvae increased with increase in conidial concentrations and time elapsed after treatment.
Keywords: Bioassays; entomopathogenic fungi; eggs; larvae; mortality; pupae; Spodoptera litura